INHIBITION OF Asystasia gangetica ETHANOLIC EXTRACT ON Porphyromonas gingivalis AND Fusobacterium nucleatum BIOFILM FORMATION - Ichsyani, Meylida; Laksitasari, Anindita; Supriyati, Supriyati; Sari, Dwi Nur Indah; Wahyudin, Wahyudin (Mandala Of Health, 2025)
Periodontal pathogens Porphyromonas gingivalis and Fusobacterium nucleatum develop a biofilm on the surface of the dental apex, causing inflammation in the teeth' supporting tissues. Asystasia gangetica has been observed for its analgesic, anti-inflammatory, and antimicrobial effect. The ethanolic extract of A. gangetica may be developed as a root canal sterilization dressing due to its benefits. This study aims to determine the inhibitory effect of ethanolic extract of A. agangetica on P. gingivalis and F. nucleatum from forming biofilm. Antibacterial activity was determined using Kirby-Bauer disk diffusion. The inhibition of biofilm formation was evaluated using microtiter plate biofilm assay with various concentrations of extract. Base on the classification of inhibition zone, ethanolic extract of A. gangetica had moderate to strong antibacterial effects on P. gingivalis at 12.5-50 mg/mL, and moderate effect on F. nucleatum at 25-50 mg/mL. Results also showed that the extract at 50 mg/mL, inhibited biofilm formation by more than 72% against P. gingivalis (p<0.05) and up to 75% against F. nucleatum (p<0.05). The value of MBIC50 was determined at 5.19 mg/mL and 7.44 mg/mL, respectively. Ethanolic extract of Asystasia gangetica has a potential inhibitory effect on P. gingivalis and F. nucleatum biofilm formation. Studies suggest more detailed approaches to a better understanding of the interactions between lead compounds and bacterial cells within the biofilm structure.